Composition‐Controlled Synthesis of Hybrid Perovskite Nanoparticles by Ionic Metathesis: Bandgap Engineering Studies from Experiments and Theoretical Calculations. Issue 42 (20th May 2019) - Roy, Mrinmoy; Vikram,; Banerjee, Sucheta; Mitra, Arijit; Alam, Aftab; Aslam, M.
Abstract: Herein a newly discovered non‐polar solvent based synthesis of MAPbX3 hybrid perovskite nanoparticles (NPs) is presented, where MA=Methylammonium and X=I, Br and Cl, as well as their mixed halide counterparts. The methodology proposed is simple and uses low‐cost commercial precursors. The conventional method of hybrid perovskite preparation requires methylammonium halide precursors and highly polar solvents. Mandatory use of polar solvents and a particular perovskite precursor makes an intermediate compound which then requires a non‐polar solvent to recover the NPs. In contrast here, a whole range of mixed halide perovskite NPs is fabricated without using a methylammonium halide precursor and a polar solvent. In this method, a non‐polar solvent is used, which provides a better platform for the particle recovery. Organic cations on the nanoparticle surface prevent degradation from water, due to their hydrophobic nature, and hence offer a stable colloidal suspension in toluene for more than three months. Ab‐initio calculations within density functional theory (DFT) predict lower formation energies compared to previously reported values, confirming better chemical stability for this synthesis pathway. Through the halide compositional tuning, these NPs exhibit a variety of emission and absorption starting from ultraviolet to near infrared (IR). The absorption spectra of various halide perovskite show a sharp band edge over the visible wavelength with high absorption coefficient. High oscillator strengths due to high excitonic binding energies combined with the simulated finite dipole transition probabilities point towards the observed high absorption. The emission spectra of mixed halide perovskites vary from 400 to 750 nm, which covers the whole range of visible spectra with sharp full‐width at half maxima. Different halide perovskite exhibit average recombination lifetime from 5 to 227 ns. Ambient synthesis, chemical robustness and tunability of emission with varying halide compositions make MAPbX3 (X=I, Br and Cl) NPs appealing for the optoelectronic applications. Abstract : Hybrid theory : A new route to hybrid perovskite nanoparticles is presented, which obviates the need for polar solvents, leading to simpler recovery, lower costs, and higher stability. Variation of the halide composition leads to tuneability of the band gap and emission.